Funding approaches for mental health services: is there still a role for clustering?. (10th August 2018) - Jacobs, Rowena; Chalkley, Martin; Aragón, María José; Böhnke, Jan R.; Clark, Michael; Moran, Valerie
SUMMARY: Funding for mental health services in England faces many challenges, including operating under financial constraints where it is not easy to demonstrate the link between activity and funding. Mental health services need to operate alongside and collaborate with acute physical hospital services, where there is a well-established system for paying for activity. The funding landscape is shifting at a rapid pace and we outline the distinctions between the three main options – block contracts, episodic payment and capitation. Classification of treatment episodes via clustering presents an opportunity to demonstrate activity and reward it within these payment approaches. We discuss the results of our research into how well the clustering system is performing against a number of fundamental criteria. We find that, according to these criteria, clusters are falling short of providing a sound basis for measuring and financing services. Nevertheless, we argue that clustering is the best available option and is essential for a more transparent funding approach for mental healthcare to demonstrate its claim on resources, and that clusters should therefore be a starting point for evolving a better funding system. LEARNING OBJECTIVES: Understand the different payment models currently being used and proposed in mental health services in England Understand the role of clustering in measuring mental health activity and providing a basis for funding Understand how a robust model of clustering can benefit the provision of mental health services DECLARATION OF INTEREST: None.